Combining pinch and energy analysis for process improvement - a case study on an aromatics complex - Abdul Manan, Zainuddin; Foo, Sheek Hian (Penerbit UTM Press, 2000)
Exergy Analysis, also known as Thermodynamic Analysis, is a tool that has been widely used to analyse the energy efficient of continuous processes. It is a powerful analysis tool that is based on the First and the Second Law of Thermodynamics. Pinch Technology, on the other hand, is a tool for optimization of a plant’s heat recovery. Pinch Analysis application however requires extensive process mass and energy balances data. Thus, it cannot provide a quick assessment of the efficiency of selected equipment or processes. Extensive literature exists on the applications of Pinch Analysis on chemical processes and Exergy Analysis on power plants for energy efficiency improvement. Study on combined Pinch-Exergy Analysis has so far been limited to power plant improvements. This work demonstrates that the powerful combination of Pinch and Exergy analysis can assist designers to pinpoint inefficiencies in specific locations in a plant and to help outline strategy to improve the energy efficiency for the plant. In this work, an aromatics plant steady state model has been developed and used as a case study. The analysis shows that the potential energy savings of up to 60% for hot utility and 20% of cold utility are achievable for the aromatics plant.